2008
DOI: 10.1091/mbc.e07-07-0639
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Srk1 by the Mitogen-activated Protein Kinase Sty1/Spc1 Precedes Its Dissociation from the Kinase and Signals Its Degradation

Abstract: Control of cell cycle progression by stress-activated protein kinases (SAPKs) is essential for cell adaptation to extracellular stimuli. The Schizosaccharomyces pombe SAPK Sty1/Spc1 orchestrates general changes in gene expression in response to diverse forms of cytotoxic stress. Here we show that Sty1/Spc1 is bound to its target, the Srk1 kinase, when the signaling pathway is inactive. In response to stress, Sty1/Spc1 phosphorylates Srk1 at threonine 463 of the regulatory domain, inducing both activation of Sr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 17 publications
0
48
0
1
Order By: Relevance
“…StyI MAPK, the Hog1 homologue in Schizosaccharomyces pombe, delays the cell cycle during the G 2 /M phase in response to osmostress by regulating Cdc25 localization (55). Interestingly, StyI regulation of Cdc25 is independent of Wee1 function, similar to the cell wall integrity checkpoint being independent of Swe1 (3,56).…”
Section: Discussionmentioning
confidence: 99%
“…StyI MAPK, the Hog1 homologue in Schizosaccharomyces pombe, delays the cell cycle during the G 2 /M phase in response to osmostress by regulating Cdc25 localization (55). Interestingly, StyI regulation of Cdc25 is independent of Wee1 function, similar to the cell wall integrity checkpoint being independent of Swe1 (3,56).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylated Srk1 blocks mitotic onset by inhibiting the activity of the Cdc25 phosphatase that is required to activate maturation-promoting factor (MPF) (LopezAviles et al, 2005;Lopez-Aviles et al, 2008). Because Sty1 both promotes and delays mitotic onset, an extra layer of regulation is likely to be needed.…”
Section: Mapk Control Of Mitotic Onsetmentioning
confidence: 99%
“…This model would predict that Srk1 would need a high threshold of activation before it becomes phosphorylated. Interestingly, the site in Srk1 that is phosphorylated by Sty1 is ARTP (Lopez-Aviles et al, 2008) (amino acid shown in bold indicates phosphorylation site), which differs from the optimal MAPK consensus sites PX(S/T)P and so might require a high level of Sty1 activity for phosphorylation and thus inhibition of mitosis.…”
Section: Mapk Control Of Mitotic Onsetmentioning
confidence: 99%
“…Spc1 also promotes meiosis by inducing the expression of the transcriptional factor Ste11, a regulator involved in sexual development (16). Under osmotic stress, Spc1 interacts with and phosphorylates the Ser/Thr kinase Srk1, which results in a transitory G 2 /M cell cycle arrest (17), while Srk1 overexpression inhibits the cell cycle arrest in G 1 , under nitrogen starvation. In addition, Srk1 has a regulatory role in meiosis, as null Srk1 mutants enter meiosis earlier than the wild-type strain (18).…”
mentioning
confidence: 99%